DRUNKONYMS IN ENGLISH (BASED ON B. FRANKLIN’S “THE DRINKER”S DICTIONARY”) - Shavladze, Thea (International Journal of Innovative Technologies in Social Science, 2023)
The article is devoted to the study of drunkonyms in English. “Drunkonym” is a linguistic term used to denote lexical units depicting a person’s alcohol intoxication. There are too many synonymous words and phrases in English for “Drunk.” Such kind of words and idioms exist in all languages, but their number is extremely big in English. There are several dictionaries called “Drunktionaries” in English. In the article one of the most famous dictionaries of this type “The Drinker’s Dictionary” by B. Franklin is scrutinized. The classification of drunkonyms is made according to different criteria (according to their degree of intensity, according to their positive or negative connotation, according to figurative language used in them). The analysis revealed that most of the drunkonyms do not describe positive attributes of character nor desirable states of mind. “Drunkeness” as a concept is of negative character but in English there are some positive lexical units denoting alcohol intoxication. The analysis also showed that many phraseological units depict an intoxicated person’s condition through idiomatic zoonyms. Besides there is a group of idiomatic drunkonyms containing toponyms, phytonyms and anthroponyms. Drunkonyms in B. Franklin’s dictionary may fall into several categories: literary, neutral and colloquial (slangy, vulgar, disphemic). Phraseological Drunkonyms are based on the following stylistic devices: metaphor, metonymy, euphemism, simile and irony.